Heterogenic bacterial resistance to low concentration of ketamine - Tomasz Jarzembowski; Agnieszka Daca; Marlena Zyśk; Wiesław Cubała; Lidia Piechowicz (Journal of Global Antimicrobial Resistance)
AIM: We aimed to evaluate the impact of sub-inhibitory ketamine concentration on enterococcal cells including changes in b-lactam resistance. BACKGROUND: It becomes clear that not only the antimicrobial drugs, designed to stop the proliferation of bacteria can fulfil that purpose. Our previous study showed that immunosuppressive drugs - tacrolimus and cyclosporine - change the expression of penicillin-binding proteins in enterococcal cells. Among others is ketamine, a substance with a 50-year-long history of anaesthetic and anti-microbial potential. However, nowadays it is used mainly in anti-depressive therapy in concentrations significantly below its minimal inhibitory concentration (MIC) for the majority of bacteria. On the other hand, it is known that even the concertation of a chemical lower than inhibitory for bacteria may change the properties of the microbe. METHODS: 27 enterococcal clinical strains were isolated as the etiological agents of infection. Each isolate was co-incubated with ketamine in a concentration equal to the maximum plasma concentration of the substance in the blood of the patient undergoing anti-depressive therapy. To measure the changes in viability of cells treated with ketamine, carboxyfluorescein diacetate succinimide ester staining followed by flow cytometry analysis was used. Changes in penicillin susceptibility were tested using an xCeLLigence RTCA instrument. RESULTS: 11 of the strains were found to be resistant to the therapeutic ketamine concentration while diversity among non-inhibited ones suggests the heterogeneity of the resistance. CONCLUSIONS: The impact of non-antimicrobial drugs on bacterial resistance should be considered as an additional treatment to increase the rate of successful antimicrobial therapy.